The last observation of the long-spined exotic Sea Urchin (Diadema setosum) in the Gulf of Antalya - Gokoglu, Mehmet; Ã‡ağÄ±ltay, Ferhat; Gürdal, Mustafa; YÄ±ldÄ±z, Alper (Universitas Malikussaleh, 2023)
Diadema setosum, a Red Sea migrant, was first identified on the shores of the KaÅŸ Peninsula in the Mediterranean. Approximately a year after this observation, the same species was reported for the second time from KonyaaltÄ± Beach in Antalya Bay. This sea urchin rapidly multiplied and expanded its distribution along the coasts of the Mediterranean and Aegean Seas, reaching as far as the Marmara Sea. Some individuals of this sea urchin, which expanded distribution to coastal areas posing a risk to swimmers, were observed to start dying in the summer months of 2022. Scuba diving surveys were conducted in five different areas with rocky and stony seabed structures in the Gulf of Antalya during the winter season (Cliffs, KonyaaltÄ± Beach, SÄ±Ã§an Island surroundings, Ã‡altÄ±cak region, and Kemer Ağva Cape), and it was determined that 99% of the D. setosum population had died in February and March. No living individuals were encountered during scuba diving surveys conducted in the same stations in April and May. In conclusion; mass mortalities have occurred in the D. setosum population in the rocky areas of the Gulf of Antalya, including the cliffs, KonyaaltÄ± beach, SÄ±Ã§an island surroundings, CaltÄ±cak region, and Kemer Ağva Cape. This study presents the first report on matter.Keywords: Diadema setosum; Gulf of Antalya; Sea urchin.